2010
DOI: 10.3354/dao02275
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Photobacterium damselae subsp. damselae strains isolated from new cultured marine fish

Abstract: The in vivo and in vitro toxicity of bacterial cells and their extracellular products (ECPs) from 16 strains of Photobacterium damselae subsp. damselae isolated from 7 epizootic outbreaks were evaluated. On the basis of their 50% lethal dose (LD 50 ) values (about 1 × 10 5 CFU), these strains may be considered as moderately virulent. However, their ECPs were strongly lethal for redbanded seabream Pagrus auriga causing fish death within 2 h post-inoculation (protein concentration ranged between 2.1 and 6.41 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 51 publications
1
59
1
4
Order By: Relevance
“…Actually, previous studies reported that the human isolate CDC2227-81 and the fish isolate RM-71 showed almost identical 50% lethal doses for mice, whereas RM-71 was more virulent for fish than CDC2227-81 (17). Other studies reported that strains lacking dly gene still showed virulence for mice and fish, indicating that dly is not a prerequisite for virulence in this bacterium (16,30,42). In addition, the extracellular products of virulent strains regardless of presence of dly gene were lethal for fish and mice, as well as cytotoxic for homeotherm and poikilotherm cell lines (16,30), suggesting that other virulence factors than Dly might play a role in the pathogenesis of this bacterium, but their nature remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, previous studies reported that the human isolate CDC2227-81 and the fish isolate RM-71 showed almost identical 50% lethal doses for mice, whereas RM-71 was more virulent for fish than CDC2227-81 (17). Other studies reported that strains lacking dly gene still showed virulence for mice and fish, indicating that dly is not a prerequisite for virulence in this bacterium (16,30,42). In addition, the extracellular products of virulent strains regardless of presence of dly gene were lethal for fish and mice, as well as cytotoxic for homeotherm and poikilotherm cell lines (16,30), suggesting that other virulence factors than Dly might play a role in the pathogenesis of this bacterium, but their nature remains unknown.…”
mentioning
confidence: 99%
“…damselae isolates. Two main distinct hemolytic phenotypes could be observed on blood agar plates, with strains showing a large hemolysis halo (LH) and strains producing a small hemolysis halo (SH), although the type strain ATCC 33539 can be described as moderately hemolytic (MH) (7,9,16,30,42). Early studies demonstrated that the P. damselae subsp.…”
mentioning
confidence: 99%
“…damselae is considered a primary pathogen of a wide range of marine animals, including wild and cultivated fish, causing losses of economical importance in marine aquaculture (1)(2)(3). In addition, this pathogen is of special concern for humans, since it can cause a highly severe necrotizing fasciitis that may lead to a fatal outcome (4,5).…”
mentioning
confidence: 99%
“…Additionally, it was shown that the ECPs from 16 strains of P. damselae subsp. damselae that were strongly lethal for redbanded seabream (Pagrus auriga) exhibited lipase, phospholipase and esterase-lipase activities among others (Labella et al, 2010). They also displayed a strong cytotoxic effect on four fish cell lines, although this effect disappeared when ECPs were heated at 100˚C.…”
Section: Extracellular Products (Ecps)mentioning
confidence: 99%
“…The virulence of the strains tested could not be related to the haemolytic activity or to the production of the toxin damselysin. Therefore, another unknown type of toxin could play an important role in the virulence mechanisms of this bacterium (Labella et al, 2010).…”
Section: Extracellular Products (Ecps)mentioning
confidence: 99%